2015
DOI: 10.1039/c5qo00116a
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of structural units of lignin promoted by persulfate through selective C–C cleavage under mild conditions

Abstract: A high selectivity and activity for the fragmentation of β-O-4 and β-1 lignin models to high-value chemicals were achieved by using persulfate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…However, the lower yield of the desired phenolic compounds was afforded (10–30 % yield), possibly due to over‐oxidization and/or the formation of low polymer. This observed result is in accordance with previous reports on the oxidative cleavage of lignin model compounds …”
Section: Resultssupporting
confidence: 94%
“…However, the lower yield of the desired phenolic compounds was afforded (10–30 % yield), possibly due to over‐oxidization and/or the formation of low polymer. This observed result is in accordance with previous reports on the oxidative cleavage of lignin model compounds …”
Section: Resultssupporting
confidence: 94%
“…The β‐1 linkage resembles the β‐O‐4 linkage but without the CO bond. Only a few works have investigated the cleavage of β‐1 linkages . The catalytic systems for the C α C β bond cleavage of the β‐O‐4 linkage are generally effective toward the β‐1 linkage .…”
Section: The Challengesmentioning
confidence: 99%
“…Thec orresponding aromatic esters were obtained in good to moderate yields.Specifically,the catalytic system can also effectively oxidize cleavage of complex lignin models with Cg-OH into corresponding esters in moderate yields.H owever,t he lower yield of the desired phenolic compounds was afforded (10-30 %y ield), possibly due to over-oxidization and/or the formation of low polymer.T his observed result is in accordance with previous reports on the oxidative cleavage of lignin model compounds. [18][19][20][21][22][23] To better elucidate the mechanism of the oxidative cleavage of secondary alcohols to esters,wefirst implemented ar adical inhibition experiments to determine whether the reaction involves free radicals.T he results showed that the radical scavengers 2,6-di-tertbutyl-4-methylphenol (BHT) or (2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) had no effect on the formation of target products (Supporting Information, Scheme S1), thus suggesting that the radical reaction process can be ruled out.…”
Section: Angewandte Chemiementioning
confidence: 99%